2005
DOI: 10.1291/hypres.28.879
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Cardiovascular Events in Japanese Hypertensive Patients with Hypercholesterolemia: Sub-Analysis of the Japan Lipid Intervention Trial (J-LIT) Study, a Large-Scale Observational Cohort Study

Abstract: Coronary events and stroke are leading causes of death in Japan. However, the effects of hypertension on the risk of coronary events and stroke have not been well established in Japanese hypercholesterolemic patients. This study aimed to determine the relationship between the risk of coronary events or stroke and blood pressure and cholesterol levels during low-dose simvastatin treatment using data from the Japan Lipid Intervention Trial (J-LIT) study (a large scale nationwide cohort study). In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…In addition, normal BP and high-normal BP individuals with high cardiovascular risks (third class) had significantly different risk levels for stroke or TIA when the assessment was based on HBP. Several previous studies conducted in the Japanese population also support the current results, even based on CBP (18,19). It seems reasonable to suppose that we should assess both hypertensives and non-hypertensives in the next version of the Japanese BP guidelines, and that the importance of HBP should be more heavily emphasized in the revised guidelines for accurate evaluation of BP risks in individuals.…”
supporting
confidence: 82%
“…In addition, normal BP and high-normal BP individuals with high cardiovascular risks (third class) had significantly different risk levels for stroke or TIA when the assessment was based on HBP. Several previous studies conducted in the Japanese population also support the current results, even based on CBP (18,19). It seems reasonable to suppose that we should assess both hypertensives and non-hypertensives in the next version of the Japanese BP guidelines, and that the importance of HBP should be more heavily emphasized in the revised guidelines for accurate evaluation of BP risks in individuals.…”
supporting
confidence: 82%
“…Here, we evaluated separately the risks of IGT for stroke and CHD using a cohort study of a Japanese population. The incidence of stroke is higher (1.5-2.5 times more) than that of CHD in Japan [23][24][25]; therefore, the risk for stroke was evaluated more precisely in the present study. However, even in a previous study of Japanese subjects, IGT was shown to be a risk factor for CVD but not for stroke [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study failed to prove a relationship between elevated baseline BNP levels and the risk of developing hypertension, indicating that additional investigation is necessary to confirm the association. Hypertension is a major risk factor for the development of cardiovascular disease (14)(15)(16)(17) and the ability to predict the onset of new hypertension is an attractive proposition (18). We hypothesized that normotensive individuals with higher plasma BNP levels have a higher probability of developing hypertension in the future.…”
Section: Does B-type Natriuretic Peptide Predict the New Onset Of Hypmentioning
confidence: 99%